Hebei loess section in the Anyemaqen Mountains, northeast Tibetan Plateau: a high‐resolution luminescence chronology. (23rd May 2018) - E, Chongyi; Sohbati, Reza; Murray, Andrew S.; Buylaert, Jan‐Pieter; Liu, Xiangjun; Yang, Long; Yuan, Jie; Yan, Wenting
Abstract : The extensive aeolian deposits of the Tibetan Plateau (TP) represent important environmental archives, recording information about the past interplay between the Asian monsoon and Westerlies and the link between dust accumulation and Quaternary glaciations. In the northeast TP, mantles of sandy loess form a distinct belt lying between 3500 and 4500 m a.s.l. on the east‐facing slopes of the Anyemaqen Mountains. However, there is little chronological information about the loess deposits in this region. This study provides a detailed chronology for loess formation in the region using luminescence dating. A total of 29 samples were collected from an 8‐m‐thick homogeneous loess section at Hebei (HB) in order to date sand‐sized (63–90 μm) quartz and K‐feldspar fractions using optically stimulated luminescence (OSL) and infrared stimulated luminescence (IRSL and pIRIR) signals, respectively. The resulting quartz and feldspar ages are in good agreement over the last 40 ka; beyond this (i.e. D e >120 Gy), the quartz age is underestimated, and the pIRIR170 feldspar ages are considered more reliable. The HB loess section records continuous environmental information from c. 50 to c. 30 ka, i.e. throughout Marine Isotope Stage (MIS) 3. Mass accumulation rates (MARs) varied considerably over this period with increased dust accumulation around c. 38 ka and after c. 32 ka; in between, and at the beginning of MIS 3 (50–40 ka), the dust accumulation rate was 50% lower. Finally, the HB section also records a MIS 2 hiatus of c. 17 ka duration, probably resulting from deflation. This study implies that loess deposition on the TP is predominantly an interglacial/interstadial phenomenon and the TP may be deflating at the same time as the Chinese Loess Plateau is accumulating, at least during MIS 2.